(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the demand for international academic exchange among students of University of Medicine and Pharmacy, Hue University and to identify factors associated with this demand. Object and methods: A cross-sectional study was conducted among 403 students of University of Medicine and Pharmacy, Hue University using a structured questionnaire. Data were analyzed with SPSS 20.0 software using Chi-square tests and OR with 95% confidence intervals. Results: The proportion of students expressing interest in participating in international exchange programs was 40.2%. The most commonly reported barriers were financial constraints (90.6%), language and cultural difficulties (75.2%), and separation from family (48.6%). Statistically significant factors associated with exchange participation included family separation, lack of program information, and complex administrative procedures. Conclusion: The demand for international academic exchange among students remains moderate, primarily limited by financial, informational, and language barriers. Enhancing institutional communication, expanding scholarship opportunities, and improving students’ foreign language proficiency are essential to promote participation and foster international integration in medical education.